Pertanggungjawaban Notaris Pengganti Terhadap Kesalahan Yang Dibuat Dalam Pembuatan Akta - Hafizha, Tsaniya; Aminah, Aminah (Fakultas Syariah INSURI Ponorogo, 2023)
Drafting legal documents is a crucial responsibility of a notary, who is accountable for the authenticity and accuracy of the legal documents they produce. However, in practice, errors or inaccuracies may occasionally occur in the drafting of legal documents, which can have serious consequences in legal agreements involving relevant parties. This journal aims to delve deeper into the accountability of substitute notaries in the context of errors that occur during the process of making deeds. This research considers the legal, ethical, and professional aspects inherent to the notary profession. The methodology employed includes literature and library research, utilizing normative legal research. The research findings elaborate on the responsibilities of substitute notaries in identifying, rectifying, and preventing errors in deed creation. Furthermore, this journal also discusses the role of notary institutions in supervising and regulating the substitute notary profession to ensure compliance with high ethical and legal standards, along with the consequences in case of errors in deed creation. This research provides essential insights for legal practitioners, notaries, and other relevant parties regarding the actions to be taken when dealing with errors in document drafting and the efforts that can be made to prevent them. Additionally, this journal contributes to the discourse on the need for improvements in the supervision and regulation of the notary profession to enhance the quality of legal services provided to the public. This research highlights the significant implications of enhancing accountability and preventing errors in deed creation among substitute notaries, aligning them with legal and ethical standards.